ANALYSIS OF THE NEEDS FOR DEVELOPING EMODULES WITH FLIPPING BOOKS AS ETHNOMATHEMATICS-BASED TEACHING MATERIALS - Pitri Oktaria Pirma; Caswita Caswita (JME (Journal of Mathematics Education), 2023)
This research is research on the development of teaching materials in the form of e-modules based on ethnomathematics. This type is a qualitative descriptive research. The research data collection instruments were form of teacher needsanalysis interview sheets, and student needs analysis questionnaires. The teaching material developed is the form of an e-module using a Flipping book. The research subjects consisted of a teacher and 28 grade VIII junior high school students. The results of the needs analysis obtained that 78.6% of students answered that they had textbooks or other guidelines but 61% ofstudents answered that they did not look for learning materials anymore only from school books, as many as 75% of students wanted to learn using teaching materials other than textbooks or worksheets, then as much as 82% answered that the learning media used by teachers didn’t contain culture in mathematical concepts, and 71% of students thought that it was necessary to use media e-modules based on ethnomathematics to learn mathematical concepts in culture. These results indicate that it needed to develop teaching materials emodules based on ethnomathematics.